The methodology of developing the interior environment of kindergartens - Abu-Hannoud, Ehab (2013)
The research work is in the area of architectural design guidelines and more particularly in the interior design of kindergartens in Palestine. The aim of this research is to enhance the quality of learning environment of kindergartens in Palestine by developing a new design and monitoring guidelines. The research focuses on the methodology of developing the interior learning environment of kindergartens, which based mainly on understanding the key players’ needs, difficulties and problems in this sector in Palestine. The study uses three international case studies from (Japan, Austria and South Africa) in addition to cases from the UK. The international studies hold general concepts that could be considered international criteria, from which the future Palestinian kindergartens building regulations can learn and take advantage, after re-moulding them in the Palestinian culture and characteristics. It is believed that, regardless of the disadvantages and difficulties of the current Palestinian kindergarten buildings, these buildings carry unique principles and characteristics that can enhance and enrich the Palestinian learning environment. Furthermore, this study has a three local case study from Palestine, which are used to make a comparison between: the Palestinian unique principles; the international principles; and the missing principles in the current Palestinian kindergarten buildings. As a result of this comparison it will be determined what should be kept or excluded from the previous three drivers, while suggesting new ‘drafts’ and recommendations. These drafts are discussed with key players to outline the main difficulties they may face in applying them or monitoring them by MOHE. This will enable the study to generate the best final recommendations that can meet the Palestinians’ needs and aspirations. These final recommendations will be considered as the base that MOHE can rely on in forming their own regulations in the future.